Diverse heliorhodopsins detected via functional metagenomics in freshwater Actinobacteria, Chloroflexi and Archaea. (4th January 2022) - Chazan, Ariel; Rozenberg, Andrey; Mannen, Kentaro; Nagata, Takashi; Tahan, Ran; Yaish, Shir; Larom, Shirley; Inoue, Keiichi; Béjà, Oded; Pushkarev, Alina
Summary: The recently discovered rhodopsin family of heliorhodopsins (HeRs) is abundant in diverse microbial environments. So far, the functional and biological roles of HeRs remain unknown. To tackle this issue, we combined experimental and computational screens to gain some novel insights. Here, 10 readily expressed HeR genes were found using functional metagenomics on samples from two freshwater environments. These HeRs originated from diverse prokaryotic groups: Actinobacteria, Chloroflexi and Archaea . Heterologously expressed HeRs absorbed light in the green and yellow wavelengths (543–562 nm) and their photocycles exhibited diverse kinetic characteristics. To approach the physiological function of the HeRs, we used our environmental clones along with thousands of microbial genomes to analyze genes neighbouring HeRs. The strongest association was found with the DegV family involved in activation of fatty acids, which allowed us to hypothesize that HeRs might be involved in light‐induced membrane lipid modifications.